2007
DOI: 10.1038/sj.jhh.1002288
|View full text |Cite
|
Sign up to set email alerts
|

Sympathoadrenergic and metabolic factors are involved in ambulatory blood pressure rise in childhood obesity

Abstract: We investigated in a young Italian obese population, the relationship between ambulatory BP (ABP) and several pathophysiological factors linking obesity to hypertension. A total of 89 obese children and adolescents underwent a 24-h ambulatory BP monitoring (ABPM) and an oral glucose tolerance test. The circulating levels of insulin, lipids, uric acid, C-reactive protein, interleukin-6, renin and aldosterone and the 24-h urinary levels of epinephrine, norepinephrine and albumin excretion rate were measured. Nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 38 publications
(44 reference statements)
2
19
0
3
Order By: Relevance
“…1,2 It is known that similar to older individuals, HT in young age coexists with features of metabolic syndrome, such as overweight/obesity, hyperinsulinaemia/insulin resistance and dyslipidaemia. [3][4][5] It is even suggested that the pathophysiologic precursors of adult HT originate earlier in life.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It is known that similar to older individuals, HT in young age coexists with features of metabolic syndrome, such as overweight/obesity, hyperinsulinaemia/insulin resistance and dyslipidaemia. [3][4][5] It is even suggested that the pathophysiologic precursors of adult HT originate earlier in life.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, one emerging notion is that sympathetic overdrive, a cornerstone characteristic of the non-dipper hypertensive, may be the underpinning of the above interactions. 21 The questions of the necessity to evaluate night BP by Ambulatory Blood Pressure Monitoring (ABPM) in all hypertensive subjects and to convert the pattern of circadian BP variation into a dipping one are still unresolved issues that require further investigation. As the strict control of hypertension could possibly result in the prevention or the reversion of its inflammatory component, another point to be addressed would be the necessity of initiation of therapies like aspirin, statins, renninangiotensin-aldosterone system inhibitors and novel b-blocking compounds with a potential effect in the reduction of the markers of inflammation and the associated cardiovascular risk.…”
Section: Non-dippersmentioning
confidence: 99%
“…13 Adjustment for height and weight rather than BMI might have been better. In addition, the survey sizes were small (less than 50 subjects per single year of age and sex category) and random variability may have resulted in spurious differences.…”
mentioning
confidence: 99%
“…At that age, these differences also matter because they may be associated with differences in the degree of sexual maturation, a factor associated with the level of BP. 13 Adjustment for height and weight rather than BMI might have been better. In addition, the survey sizes were small (less than 50 subjects per single year of age and sex category) and random variability may have resulted in spurious differences.…”
mentioning
confidence: 99%